In-House Software Development for Data Visualization of Random Motion Configuration of Particles in Fluid - Septian Ulan Dini; Sparisoma Viridi (Institut Teknologi Bandung, 2021)
This study aims to develop in-house software for data visualization program using Python programming language. Implement a simple algorithm and use the matplotlib library for 2D plotting. The results of development of this program were tested using a dataset from random motion simulation results of many particles modeled by two-dimensional circle shape and the diameter size as D. Data visualization in the form of particles configuration then confirmed with the particles configuration of the simulation results. Based on the test, it is found that the particles configuration results of the visualization are same as the configuration of the simulated particles. This shows that the data visualization program that has been developed can be used to process other data stored in a predetermined data format.